Czech Republic Country Report - Gillis, Mark (2000)
The institute of referendum has not enjoyed a particularly active history in the Czech Republic (and prior to that state's birth on 1 January 1993, in the Czechoslovak Republic). It has existed both on the nation-wide level and locally, and it is on the latter level that it has laid more roots in the proper sense. The institute of referendum on a nation-wide level has been for all intents and purposes virtually non- existent. Although it has existed in the legal order at various times since the establishment of the Czechoslovak Republic in 1918, it has not existed at all times, and during periods when there was a positive legal basis for it, it was always regulated in the narrowest possible sense. The local referendum, which will be dealt with in turn, has had a more active career, but by its very nature has not had broad impact on political or legal affairs either.